EQUITABLE EDUCATION AND GHETTOIZED VOICES : a deficit ideology of poverty in the caribbean - DOUGLAS, JUNE A. ([S.l.] : ROUTLEDGE, 2024)
This book centres the voices of a group of marginalized residents in Grenada's ghetto to examine questions of poverty and survival and how, within this context, residents are able to focus on improvement and equity for their children through education. As a developing nation in the Caribbean influenced by both its British colonial past and its proximity to the United States, Grenada is still rife with poverty, and access to quality education is limited. The author examines this tradition of the ghetto as the centre of community and a force for positivity among youth, and develops a theory of education and deficit poverty through examples of citizens living in a developing state. Using functionalism, life course, and other systems theories, the book examines how institutions can support communities, and, in contrast, how families in poverty support themselves in the wake of system failure, to the extent that some children become successful university graduates, entrepreneurs, and world travellers. A cutting analysis of the development of equity through education in states left behind by colonialism and globalisation, this book offers new understandings of survival and criminality caused by deficit poverty. It will appeal to scholars, faculty, and researchers with interests in international education, education and globalisation, small island states, life course theory, systems theory, and anthropology.
Keywords: Poor children -- Education -- Grenada; Educational equalization -- Grenada; EDUCATION / General; SOCIAL SCIENCE / Anthropology / Cultural; SOCIAL SCIENCE / Criminology